Dual targeting carbonic anhydrase inhibitors as promising therapeutic approach: a structural overview - D’Ambrosio, Katia; Di Fiore, Anna; Langella, Emma (Frontiers in Molecular Biosciences, 2025)
The dual-target inhibitor strategy is an evolving approach that holds great potential for treating complex diseases by addressing their multifactorial nature. It can enhance therapeutic outcomes, reduce side effects and avoid the emergence of drug resistance, particularly in conditions like cancer, inflammation and neurological disorders, where multiple pathways contribute to disease progression. Identifying suitable targets for a dual inhibitor approach requires a deep understanding of disease biology, knowledge of critical pathways, and selection of complementary or synergistic targets. Human carbonic anhydrases (hCAs) have been recognized as suitable drug targets for this therapeutic approach. These enzymes play a key role in maintaining pH balance, ion transport, and fluid regulation across various tissues and organs and their dysregulation has been associated to a variety of human pathologies. Consequently, the inhibition of hCAs combined to the possibility to modulate the activity of a second molecular target represents a promising way for developing more effective drugs. In this mini-review, we aim to present an overview of the most significant structural results related to the development of novel therapeutics employing hCA inhibitors as dual-targeting compounds for the treatment of complex diseases.